Air Pollution in Ventura County 1971 - Newton Friedman::::::; Richard W. Drisko::::::; Peter J. Hearst::::::; Duane A. Lea::::::; Roger Helvey::::::; Phillip C. White::::::; Mrs. Bernard Blat:::::: (1971)
A report detailing the presence of air pollution in Ventura County and different factors that contribute to it. Also details possible methods for improving air quality.